Comic-based Worksheet to Enhance Students' Interest in Learning Civic: a Study in Charis Elementary School Grade IV - Kusumaningrum, Shirly Rizki; Istiqomariyah, Ernita; Ismawati, Mega Yuniar; Sulisyowati, Sulisyowati; Atho’urrohman, Wifqi; Lestari, Wiji (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This research aims to develop comic-based Learner Worksheets (LKPD) as learning media in Citizenship subjects for grade 4 students of SD Kristen Charis Malang. Comic-based learning media was chosen based on a needs analysis that showed students were more interested and motivated to learn with interesting visual media. The research method used is Research and Development (RnD) with the ADDIE model which consists of five stages: analysis, design, development, implementation, and evaluation. Media validation by material experts and design experts showed very practical results, with validation scores of 88% and 93%, respectively. Limited trials were conducted on 11 grade 4 students and obtained positive responses. The evaluation results showed an increase in students' average score from 90 to 95 after using the comic-based LKPD, with the majority of students reaching the “proficient” category. This study concludes that comic-based LKPD is effective in increasing students' interest and understanding in learning Citizenship. This LKPD is expected to be an alternative to innovative learning media that supports the teaching and learning process at the elementary school level.Keywords. LKPD; comic; interest in learning